The Effect of Using Virtual Reality Media Obak Delik on Improving the Spatial Visual Abilities and Critical Thinking of SMAN 1 Tuban Students - Anggun Winata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
One of the chemistry concepts that students often get low learning outcomes in class XI is the concept of molecular shape. Many students have difficulty describing the shape of molecules and this causes students to misunderstand molecular shapes because the shape of molecules is abstract and cannot be observed directly using the sense of sight. The research aims to determine the effect of using OBAK DELIK virtual reality media on the visual spatial and critical thinking abilities of students at SMA N 1 Tuban. The research used a one group pretest posttest design to determine visual spatial abilities and critical thinking abilities. Analysis of research data was carried out by analyzing diagnostic test results using the n-gain score. The results of research using OBAK DELIK media concluded that students' visual spatial and students' critical thinking abilities experienced a fairly effective increase with an n-gain of consecutively 0.621 and 0.618